Optimization of mosquitocidal toxins production by Lysinibacillus sphaericus under solid state fermentation using statistical experimental design - El-Bendary, Magda A.; Elsoud, Mostafa M. Abo; Mohamed, Sahar S.; Harmed, Shimaa R. (Acta Biologica Szegediensis, 2016)
Taguchi’s experimental design of surface response methodology was applied to optimize the culture medium conditions for Lysinibacillus sphaericus (Ls) mosquitocidal toxins production under solid state fermentation (SSF). The predicted results of this design revealed that the optimum culture medium conditions for the maximum mosquitocidal activity against second instar Culex pipiens larvae were: 3.08 ± 0.05% substrate concentration, 33 ± 1.5% moisture content, 7.8 ± 0.1 initial pH, 1.35 ± 0.15% (5.7 × 107 CFU) inoculum size and 5.9 ± 0.2 days incubation period. Sporulation titer of Lysinibacillus sphaericus (Ls 14N1) and mortality percentage of second instar Culex pipiens larvae of the fermented culture under these conditions were 2.8 × 1010 CFU/g fermented culture and 97.5 ± 1%, respectively. The results of practical validation of the design were incomparable with the mathematical results. Sporulation titer was 2.7 × 10 10 CFU/g fermented culture; LC50 was 2.8 × 10-5 final fermented culturedilution and toxin protein concentration was 2.24 mg/g fermented culture.